A aprendizagem da leitura: atuações educativas de êxito na educação de jovens e adultos - Ferreira, Letícia (2019)
The mastery of reading is a fundamental competence for the development others academic and social education in the Information Society. National and international evaluations, in their scope, explain before-mentioned competence, their abilities, and contents. Youth and Adult Education, in this context, deserves special consideration, since it supports people who have reached young and adult life without mastering this fundamental instrument. Thus, the present study aims to verify the results of two successful educational actions -Interactive Groups and Dialogic Literary Gatherings - for the learning of reading of students of the second segment of the Youth and Adult Education, taking as parameters the most anticipated descriptors in the international tests (Program for the International Assessment of Adult Competencies - PIAAC and the Program for International Student Assessment - PISA), and national ones (National Exam for Certification of Skills of Young and Adults - Encceja -, and the evaluations of the Basic Education Assessment System - Saeb). As a case study with the use of communicative methodology, the research will resort to observation techniques, interviews and recorded communicative discussion groups. The data validation will be performed using communicative technique with communicative discussion group. With this research, it is hoped to announce possibilities that support the learning of the reading by Youth and Adult Education students.